2016
DOI: 10.1016/j.catcom.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentadienyliron dicarbonyl dimer: A simple tool for the hydrosilylation of aldehydes and ketones under air

Abstract: International audienceThe readily available iron complex [CpFe(CO)2]2 (1) exhibits good catalytic activity in the hydrosilylation of aldehydes and ketones in the presence of diethoxymethylsilane. The procedure described is air-tolerant and applicable to a wide range of substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In 2016, Jung et al reported the successful application of the readily available iron complex [CpFe(CO) 2 ] 2 as a catalyst for the hydrosilylation of aldehydes and ketones. 68 Optimized conditions required a 5 mol % loading of the iron precursor, in the presence of 2 equiv of (EtO) 2 MeSiH, at 100 °C during 24 h. Remarkably, the reaction worked well under air and no solvent was needed either. Under these conditions, both aldehydes and ketones (most of them aromatic) afforded excellent or quantitative conversions.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…In 2016, Jung et al reported the successful application of the readily available iron complex [CpFe(CO) 2 ] 2 as a catalyst for the hydrosilylation of aldehydes and ketones. 68 Optimized conditions required a 5 mol % loading of the iron precursor, in the presence of 2 equiv of (EtO) 2 MeSiH, at 100 °C during 24 h. Remarkably, the reaction worked well under air and no solvent was needed either. Under these conditions, both aldehydes and ketones (most of them aromatic) afforded excellent or quantitative conversions.…”
Section: Iron-based Catalystsmentioning
confidence: 99%